The Relationship between Parental Behavior and Premature Loss of Primary Teeth at SD No. 3 Benoa - Gusti Ayu Dinda Arya Kirana; Mia Ayustina Prasetya; Louise Cinthia Hutomo; Luh Wayan Ayu Rahaswanti (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Untreated caries are the main cause of premature loss of primary teeth. Children generally prefer cariogenic foods, but this is not balanced by oral health maintenance behavior. This is because children do not understand the importance of maintaining their oral health. This is where parental behavior is needed to provide guidance and supervision to children in maintaining the health of their oral cavity. Based on this, the author is interested in examining the relationship between parental behavior and premature loss of primary teeth in students aged 6-8 years at SD No. 3 Benoa. Material and Methods: This study used an analytical observational method with a cross-sectional approach. The sample in this study was a dyad (parents and students) totaling 103 respondents. Result and Discussions: The study show that parental behavior is in the "sufficient" category, and there are quite many children experiencing premature loss of deciduous teeth. in children at SD No. 3 Benoa. There was a significant relationship between parental behavior regarding children's dental health and the incidence of premature loss of primary teeth in children, with a p-value of 0,000 (p-value < 0,05). Conclusion: There is a relationship between parental behavior regarding children's dental health and premature loss of primary teeth among 6-8-year-old students at SD No. 3 Benoa.